Czech refugees in Cold War Canada - Raska, Jan (Studies in immigration and culture, 2018)
Explores how Cold War Czechoslovakian migrants to Canada joined or formed ethnocultural organisations to help in their attempts to affect developments in Czechoslovakia and Canadian foreign policy towards their homeland.